Answer:
The equation is y = 3x - 1
Step by Step Explanation:
Ok, so your first step in solving this would be substituting m in the equation with the slope, since m represents the slope. So then you would have y = 3x + b. Now, to find b, you would have to substitue the point (1,2) into the equation. You would replace 2 with y since that's the y coordinate, and 1 with x since that's the x coordinate. Then you have 2 = (3*1) + b. Now, you solve for this. You get 2 = 3 + b. Isolating the variable b, you have b = -1. So, the result is y = 3x - 1. That's your answer